Resilient artificial intelligence, secure digital ecosystems, and intelligent computing for a connected future - Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This editorial introduces the articles published in Volume 42, Number 3, June 2026 of the Indonesian Journal of Electrical Engineering and Computer Science (IJEECS), highlighting recent advances and emerging research directions in artificial intelligence, cybersecurity, intelligent computing, and digital transformation. The published studies span a broad range of topics, including machine learning, intelligent analytics, healthcare technologies, computer vision, cryptography, privacy-preserving systems, Internet of Things (IoT) security, cloud computing, distributed optimization, blockchain applications, and decentralized digital platforms. Emerging trends highlighted throughout this issue include foundation and multimodal AI models, AI-enabled cybersecurity, privacy-preserving machine learning, Zero-Trust architectures, edge intelligence, decentralized computing, and digital trust ecosystems. Collectively, these contributions underscore the growing importance of resilient artificial intelligence and secure digital infrastructures in enabling adaptive, efficient, and trustworthy connected environments. The increasing integration of intelligence, security, resilience, and human-centered design principles reflects the evolving requirements of next-generation technologies that support sustainable innovation, economic development, and societal well-being. The research presented in this issue provides valuable perspectives on the opportunities and challenges associated with building secure, resilient, and intelligent digital ecosystems for an increasingly interconnected future.